2020
DOI: 10.1371/journal.pone.0230216
|View full text |Cite
|
Sign up to set email alerts
|

Activity and social interactions in a wide-ranging specialist scavenger, the Tasmanian devil (Sarcophilus harrisii), revealed by animal-borne video collars

Abstract: Observing animals directly in the field provides the most accurate understanding of animal behaviour and resource selection. However, making prolonged observation of undisturbed animals is difficult or impossible for many species. To overcome this problem for the Tasmanian devil (Sarcophilus harrisii), a cryptic and nocturnal carnivore, we developed animalborne video collars to investigate activity patterns, foraging behaviour and social interactions. We collected 173 hours of footage from 13 individual devils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…Spatial segregation at the home range level did not occur between devils and quolls, nor did we observe strong fine-scale patterns of avoidance in core area placement. In a different study that radio-tracked devils and quolls to their dens during the day, we found a quoll's maternal den only 400m away from a devil's maternal den (Andersen et al 2020). This further supports that there is little core area segregation between the two species.…”
Section: Interspecific Spatial Partitioningsupporting
confidence: 68%
See 2 more Smart Citations
“…Spatial segregation at the home range level did not occur between devils and quolls, nor did we observe strong fine-scale patterns of avoidance in core area placement. In a different study that radio-tracked devils and quolls to their dens during the day, we found a quoll's maternal den only 400m away from a devil's maternal den (Andersen et al 2020). This further supports that there is little core area segregation between the two species.…”
Section: Interspecific Spatial Partitioningsupporting
confidence: 68%
“…Therefore, the differences in temporal activity and movement patterns could be attributed to the different foraging strategies of devils and quolls. Devils are pounce‐pursuit predators (Jones 2003) that hunt using a moving search (Pemberton 1990) but scavenge more than they hunt at our study site (Andersen et al 2020). Their foraging strategy may be to cover sufficient distance in a night to find food and then return to a den.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to camera miniaturization, animal-borne videography can obtain information about the ecology (diet, habitat use) and behavior (mate selection, threat avoidance) that could be critical for conservation. For example, video loggers have been deployed to study ecology and behavior—for example, on crows (Rutz and Troscianko 2013 ) and Tasmanian devils (Andersen et al 2020 ). So-called AVEDs (animal-borne video and environmental data collection systems) integrate environmental sensors (e.g., audio, location, temperature, acceleration).…”
Section: Animal-borne Devices: Biologging and Biotelemetrymentioning
confidence: 99%
“…While its range historically extended throughout continental Australia, it is now only found in the wild inhabiting the island state of Tasmania, located south of mainland Australia across the Bass Strait ( 1 , 3 , 4 ). Weighing ~8–10 kilograms for males and 6–7 kilograms for females, the Tasmanian devil is a pounce-pursuit predator, forager, and facultative scavenger ( 1 , 5 , 6 ). While younger devils favor a diet of smaller mammals, birds, amphibians, reptiles, and insects, as individuals age their diet shifts to primarily macropods such as Red-necked wallabies ( Notamacropus rufogriseus ) and Rufous-bellied pademelons ( Thylogale billardierii ), both as carrion and live prey ( 1 , 2 , 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%